A Comparative Study of the Emotional Metaphors of Chinese-Korean Idioms for Body Parts - Zhang, Xinyu (Journal of Education and Educational Research, 2023)
Metaphor is a powerful tool for human beings to understand and express abstract concepts. Both Chinese and Korean have idioms for body part metaphors based on people’s long-term cultural experiences. This paper uses documentary and inductive methods to analyze the similarities and differences between Chinese and Korean body part metaphors in terms of metaphor type, high cognitive site, and mapping pattern based on comparing basic semantics.